Retroperitoneoscopic Dismembered Pyeloplasty for Ureteropelvic Junction Obstruction: Modification of the Procedure and Our Experience - Ou, zhen-yu; Chen, jin-bo; Chen, Zhi; Chen, Min-feng; Liu, Long-fei; Zhou, xu; Li, Yang-le; Qi, Lin; Zu, Xiong-bing (Urology Journal, 2014)
Purpose: To report a modified retroperitoneoscopic dismembered pyeloplasty technique and its application in the treatment of ureteropelvic junction obstruction (UPJO). Materials and Methods: From June 2010 to March 2012, retroperitoneoscopic dismembered pyeloplasty was performed in 46 patients with UPJO. Briefly, the renal pelvis was incised in the anterior aspect instead of the lateral aspect, and proximal ureter was spatulated with incision on its posterior wall. After adequately trimming, two layers of ureteropelvic anastomosis respectively lay on left and right side of one laparoscopic plane other than two different planes. In our refined procedure, the difficulty of intracorporeal suturing was greatly decreased. Data from 19 months mean follow-up were analyzed to evaluate the surgical outcomes. Results: All operations were completed without open conversion. The mean operative time, estimated blood loss, and postoperative hospitalization stay were 108 min (75 to 155 min), 30 mL (15 to 60 mL) and 4 days (2 to 9 days), respectively. No intraoperative complications were occurred. Postoperative complications included 2 cases of minor abdominal wall hematoma and 1 case of transient postoperative anastomotic leakage for 8 days, which all were successfully treated by conservative management. A mean follow-up of 19 months (12 to 36 months) was performed which showed a success rate of 97.8%. One case (2.2%) underwent open surgery for persistence UPJO two months later. Conclusion: Our modification to the retroperitoneoscopic dismembered pyeloplasty procedure is technically feasible and reliable with low complications. It could be implemented as a useful alternative technique to greatly decrease the difficulty of this procedure.